Relationship between Heightened Level of Aggression and Lower Digit Ratio in a Cohort of Children in Conflict with the Law - Isyaku Gwarzo Mukhtar; Hassan Sani Umar; Safiyyu Mujitapha Umar (Archives of Medicine and Health Sciences)
Background and Aim: Digit ratio (2D:4D) has been linked to prenatal exposure to androgen and by implication, aggression, however, results have been inconsistent. The aim of this study was to determine the relationship between 2D:4D and family income with measures of aggression among children in conflict with the law in Northern Nigeria. Materials and Methods: One hundred and twenty participants aged 12–17 years (median = 15) consisting of 60 male children in conflict with the law at a remand home in Northern Nigeria and 60 age-matched normal controls were randomly recruited. Buss–Perry Aggression Questionnaire was used to assess aggression, whereas 2D:4D was measured directly on the second and fourth fingers. Data were analyzed on SPSS version 23.0. P ≤ 0.05 was set as significance. Results: Of the 60 children in conflict with the law, 10% had a history of substance abuse; 50% were first-time offenders; 70% were involved in theft, 22% in fight, and 8% in physical assault. Children in conflict with the law had significantly lower years of education (P ≤ 0.001), r2D:4D (P = 0.003), and l2D:4D (P = 0.047) but higher family income (P ≤ 0.001) and aggression scores (P ≤ 0.001). Among the participants as a whole, education was negatively (P < 0.001), whereas family income was positively (P < 0.001), correlated with aggression; r2D:4D was positively correlated with physical (P = 0.023), verbal (P < 0.001), total aggression (P = 0.002), and anger (P < 0.001); l2D:4D was negatively correlated with physical aggression (P = 0.050) and hostility (P = 0.037). Among children in conflict with the law, l2D:4D was positively correlated with anger (P < 0.001), whereas education was negatively correlated with hostility (P = 0.015). Conclusion: Children in conflict with the law are associated with a heightened level of aggression and shorter 2D:4D. Aggression is influenced by education and family income, whereas the relationship between aggression and 2D:4D is unclear.